PERAN LAYANAN BIMBINGAN KLASIKAL DENGAN METODE WINDOW SHOPPING TERHADAP PEMAHAMAN KONSEP DIRI PESERTA DIDIK KELAS XI SMK NEGERI 1 MALANG - Melia Yulanda (Universitas Negeri Malang, 2024)
This research aims to determine the role of classical guidance services using the window shopping method in understanding the self-concept of class XI students at SMK Negeri 1 Malang. This research is qualitative research which produces descriptive data in the form of written words originating from the author's observations regarding the behavior of the subjects being observed. The data obtained in this research is data resulting from observations and open interviews with students. The subjects in this research were students of class XI Accounting 3 at SMK Negeri 1 Malang. The results of this research show that classical guidance services using the window shopping method for understanding the self-concept of class XI students at SMK Negeri 1 Malang have a good role in increasing students' understanding of the topics discussed. Thus, the use of innovative methods such as the window shopping method is very important to continue to be developed, especially in the implementation of guidance and counseling services so that students have a deep understanding of social problems and achieve optimal developmental tasks.